Toward a Green Transition: Unravelling the Impact of Innovation, Urban Dynamics, and Economic Expansion on CO? Emissions in BRICS - Waqar Ahmed; Muhammad Munsif; Rameez Akbar Talani; Ramez Raja (iRASD Journal of Energy & Environment)
Environmental degradation from growing carbon dioxide (CO?) emissions now stands as a significant worldwide issue that impacts regions undergoing quick economic expansion. The BRICS nations, which include Brazil as well as Russia, India, China and South Africa, create 45% of global CO? emissions while generating 18% of world GDP, positioning them as key participants in climate discussions at the international level. A statistical analysis evaluates the permanent and temporary relationships between technological innovation and urbanization and economic growth on CO? emission levels among BRICS nations using World Development Indicators (WDI) annual data from 1990 to 2023. Results from PMG-ARDL modelling demonstrate that both technological innovation and consumption of renewable sources actively diminish CO? emission patterns during extended periods, although economic growth helps reduce emissions when certain limitations arise. The relationship between urbanization and the environment becomes difficult to predict since it worsens emissions and demonstrates the intricate relationship between progress and sustainability. According to these results, future sustainability demands immediate implementation of advanced sustainable technologies and proper urban expansion management strategies.